Implementation Of Islamic Religious Education In The Character Forming Of Students At SMA Muhammadiyah 01 Medan - Pika Handayani; Raihan Tasnim; Selvi Regita (Al-Ulum: Jurnal Pendidikan Islam, 2022)
This study examines the application of Islamic religious education in the formation of student character at SMA Muhammadiyah 01 Medan. The type of research used is qualitative research. The primary data source in this study were Islamic Religious Education Teachers. Data collection techniques in this study using observation and interviews. The results of the study found that the application of Islamic religious education learning in order to shape the character of students at SMA Muhammadiyah 01 Medan, namely by habituation in the form of habituation of good behavior, habituation of praying in congregation in the school prayer room, saying greetings when entering class, and reading "basmalah" and "hamdalah" when starting and ending the lesson. In addition, there is direct practice in learning Islamic religious education, including: practice in managing corpses.